2020
DOI: 10.1002/ps.5805
|View full text |Cite
|
Sign up to set email alerts
|

Optimal clutch size for quality control of bisexual and Wolbachia‐infected thelytokous lines of Trichogramma dendrolimi Matsumura (Hymenoptera: Trichogrammatidae) mass reared on eggs of a substitutive host, Antheraea pernyi Guérin‐Méneville (Lepidoptera: Saturniidae)

Abstract: BACKGROUNDTrichogramma dendrolimi has been widely used in augmentative biocontrol of lepidopteran pests in China. In mass production of T. dendrolimi using Antheraea pernyi eggs as substitutive hosts, which are large in size, as clutch size is a parameter of importance to produce high quality parasitoids. Here, we aimed to determine the optimal clutch size for the bisexual Wolbachia‐uninfected line (TdB) and Wolbachia‐infected thelytokous line (TdT) of T. dendrolimi reared on A. pernyi eggs.RESULTSA medium clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…Vavre et al (1999) also reported the presence of the A subdivision of Wolbachia increases fecundity of Trichogramma bourarachae Pintureau and Babault. However, others showed Wolbachia has negative effects on host fitness in most occasions, including lower emergence rate, shorter longevity, smaller body size, and lower fecundity, when compared to their uninfected counterparts (Stouthamer and Luck, 1993;Hohmann et al, 2001;Tagami et al, 2001;Miura and Tagami, 2004;Russell and Stouthamer, 2011;Zhou et al, 2020). Previous studies also found that Wolbachia is the factor that causes the occurrence of intersex (Bowen and Stern, 1966;Beserra et al, 2003;Tulgetske and Stouthamer, 2012;Ning et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Vavre et al (1999) also reported the presence of the A subdivision of Wolbachia increases fecundity of Trichogramma bourarachae Pintureau and Babault. However, others showed Wolbachia has negative effects on host fitness in most occasions, including lower emergence rate, shorter longevity, smaller body size, and lower fecundity, when compared to their uninfected counterparts (Stouthamer and Luck, 1993;Hohmann et al, 2001;Tagami et al, 2001;Miura and Tagami, 2004;Russell and Stouthamer, 2011;Zhou et al, 2020). Previous studies also found that Wolbachia is the factor that causes the occurrence of intersex (Bowen and Stern, 1966;Beserra et al, 2003;Tulgetske and Stouthamer, 2012;Ning et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
“…Considering these two opposite hypotheses, an important question that should be tested arises: is the effect of Wolbachia on the fitness of Trichogramma offspring positive or negative in superparasitised hosts? Although previous studies have shown that Trichogramma infected by Wolbachia have higher probability for superparasitism (Huigens et al, 2004b;Farahani et al, 2015;Zhou et al, 2019bZhou et al, , 2020, the fate of Trichogramma offspring in the superparasitised host is still unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all the Trichogramma species, Trichogramma dendrolimi is considered an important egg parasitoid of a broad range of pests [36]. In China, the use of T. dendrolimi for controlling Lepidopteran pests is particularly inexpensive due to it being reared on the eggs of Chinese oak silk moth ( Antheraea pernyi ), which is easy to obtain from farmers who rear and collect cocoons of A. pernyi for the textile industry and can support the development of approximately in the tens to hundreds of offspring wasps per egg [7–10]. Therefore, the inundative release of T. dendrolimi wasps is an increasingly important, efficient, and environmentally friendly measure to control Lepidopteran pests that has been applied across millions of hectares annually in the crop-producing areas of China [2].…”
Section: Introductionmentioning
confidence: 99%
“…As important biological control agents, the biological characteristics of Trichogramma spp. have been studied in detail [2,10,11], and current investigations should focus on the molecular biology of Trichogramma . Although the whole genomes of Trichogramma , including T. pretiosum, T. brassicae , and T. evanescens , have been well annotated [12–14], the regulatory mechanisms of these tiny parasitoids is poorly researched.…”
Section: Introductionmentioning
confidence: 99%